Analysis of Campus Sustainability Using Graphical Assesment of Sustainability in University (GASU) Method (A Case Study in Industrial Engineering Department, Diponegoro University) - Novie Susanto, Benraen Pirogo, Zodieka Loventa Z, Nurjana Sigiro, Winona Zevvlin (USIM, THAMKAM, KHON KAEN, UMY, 2016)

(untitled)
A preliminary study shows that Industrial Engineering department in Diponegoro University has some environmental problems, such as the lack of green open spaces, the high consumption of electrical energy and the unorganized waste management. The absence of a special institution to deal with the environmental conditions of the campus and the lack of a budget specifically allocated for campus sustainability are also specific problems in campus sustainability. Hence, there are need for an assessment of the campus sustainability in Industrial Engineering Department of Diponegoro University. This paper aims at evaluating the campus sustainability of Industrial Engineering department. This study uses 4 criteria; they are profile, environmental, social and educational. These criteria are detailed in 15 assessment categories. For each category, there are assessment for expectation and factual performance of the campus. The method used in this study is Graphical Assessment of Sustainability in University (GASU). This method provides a systematic way and to systematically assess the indicators available, as well as the performance of which is then used to prepare a sustainability report. There are 30 respondents in this study with the age range of 18-22 years old. Of the four criteria assessed dimensions, the educational and social aspect have the highest value with the ratio of fulfillment of above 70 percent, while the environmental and the profile aspects have values close to 60 percent. These shows that for the educational aspects of Industrial Engineering of Diponegoro University have run the role of teaching, research and service with good labor practices (Employees and Lecturers). It also supports (appropriate) social sustainability. On the other hand, although the profile and environmental aspects are included in the rather high but needed a development and improvement in both aspects. Generally, Industrial Engineering department of Diponegoro University has 67.7% level of sustainability. It means the level of campus sustainability of Industrial Engineering Department of Diponegoro University is rather high (>60%). However, there are still necessity to improve some various aspects such as the lack of sewage treatment and garbage issues, hygiene and sanitation services, as well as maintenance of the campus website.